Neural control of cerebral blood flow: scientific basis of scalp acupuncture in treating brain diseases - Jin, Guan-Yuan; Jin, Louis Lei; Jin, Bonnie Xia; Zheng, Jin; He, Belinda Jie; Li, Shi-Jiang (Frontiers in Neuroscience, 2023)
Scalp acupuncture (SA), as a modern acupuncture therapy in the treatment of brain diseases, especially for acute ischemic strokes, has accumulated a wealth of experience and tons of success cases, but the current hypothesized mechanisms of SA therapy still seem to lack significant scientific validity, which may not be conducive to its ultimate integration into mainstream medicine. This review explores a novel perspective about the mechanisms of SA in treating brain diseases based on its effects on cerebral blood flow (CBF). To date, abundant evidence has shown that CBF is significantly increased by stimulating specific SA points, areas or nerves innervating the scalp, which parallels the instant or long-term improvement of symptoms of brain diseases. Over time, the neural pathways that improve CBF by stimulating the trigeminal, the facial, and the cervical nerves have also been gradually revealed. In addition, the presence of the core SA points or areas frequently used for brain diseases can be rationally explained by the characteristics of nerve distribution, including nerve overlap or convergence in certain parts of the scalp. But such characteristics also suggest that the role of these SA points or areas is relatively specific and not due to a direct correspondence between the current hypothesized SA points, areas and the functional zones of the cerebral cortex. The above evidence chain indicates that the efficacy of SA in treating brain diseases, especially ischemic strokes, is mostly achieved by stimulating the scalp nerves, especially the trigeminal nerve to improve CBF. Of course, the mechanisms of SA in treating various brain diseases might be multifaceted. However, the authors believe that understanding the neural regulation of SA on CBF not only captures the main aspects of the mechanisms of SA therapy, but also facilitates the elucidation of other mechanisms, which may be of greater significance to further its clinical applications.